Diverging historical development of migration in Southeastern Europe since 1950 - Attila Melegh (Hungarian Demographic Research Institute, 2013)
In the beginning of the period under discussion each of the countries in the region was either following European patterns of emigration or was actually serving as a migratory target (for instance in the case of Moldova). In the 1970s and 1980s (in other words well before the actual collapse of state socialism) diverging patterns began to emerge the differences between which became acute after the collapse. Some of the sub-regions (the Balkans and the region around the Black Sea within the Soviet Union) actually became sources of migrants, while others, most notably Italy and Austria became destination countries of larger number of migrants. This is a distinctive story of the construction of inner dependency within a larger region the countries of which had a great deal in common, and this process needs to be analyzed with particular care. Thus smaller meaningful historical, geographic regions can be constructed on the basis of migratory patterns. These regions do not follow the “classic” divisions, and the state socialist and capitalist local histories are related to one another, regardless of divergences. State socialism was not isolated from global flows, and, more importantly, it partially reproduced global hierarchies and had its own effects on international migration. In a modified form, the world system approach is helpful in furthering an understanding of longer term developmental patterns. In the case of state socialist economies, the direct intervention of world capitalism had a longlasting impact on the migratory links between the countries within the region under discussion. Actually, most of the former state socialist countries in the region became dependent on remittances, as shown by Böröcz (Böröcz 2012). When state socialism collapsed in the late 1980s, the economies of the countries of the region were based on a huge industrial sector. Countries that were unable to counterbalance the collapse of local industry became sending countries and were partially re-ruralized and partially pushed into large scale emigration. Thus the break-up of socialism also did not have a uniform impact on the countries in question, and the impact also depended on historical developmental hierarchies and the related ability of the various countries to regain some of the losses in the industrial sector with gains in the service sector. The analysis offered here lends credence to the neoclassic macroeconomic theory of migration, but following Böröcz and de Haas I argue that its validity with regard to per capita GDP differentials is strengthened if it is linked to positions in global hierarchies (Böröcz 2009; de Haas 2010). It thus needs to be re-contextualized into a world system approach. The key point is that it is not simply GDP differentials that matter, but rather relative positions within the global economy, which themselves are in part the results historical processes and linkages. In other words, one needs to go back to the theories of global structural changes, which is the subject matter of global history and the literature on development. In addition, I have also argued that global hierarchies and the positions of a given country in these hierarchies may well be fairly accurately perceived by the local and migrant populations. It seems that a more direct link can be found between global structures and behaviors in the perception of global hierarchies. People seem to have ideas of developmental scales that can very clearly linked to actual per capita GDP figures. Thus people might well be aware of global inequalities and may even have clear ideas of complex sequences that might also orientate them in their decisions regarding migration. This hypothesis, however, merits further research, especially from the perspective of how positions in global hierarchies are perceived by people considering emigration.
Keywords: B24; 300; Internationale Migration; Auswanderung; Migrationspolitik; Wanderungsstatistik; Ungarn